A public relations programme for the bone marrow donor programme. - Chua, Jael Wei Wei. (2009)
Established in “1993, the Bone Marrow Donor Programme (BMDP) is a nonprofit voluntary organisation which needs financial support to fulfill its mission of helping patients in need of a marrow transplant find a suitable donor match. The BMDP’s humanitarian mission inspired the authors to undertake this project and to design a public relations programme for the organisation.